The wild wild web: anonymity and racial prejudice in online culture - Lawless, Tiffany Jo (Kansas State University, 2019)
Research has shown people view some anonymous communication as less honest (e.g., Bergstrom, 2011), but some as more honest (e.g., Sticca & Perren, 2012), than identifiable communication. This discrepancy may be due to whether the target of a post is a group of people or an individual. Across two studies, I examined the effects of specificity of target on perceptions of honesty in prejudiced speech by manipulating whether posts appeared to be posted anonymously/identifiably and whether the content targeted a racial group/named individual in a counterbalanced within-groups design. In Study 2, I also manipulated whether posts were public/private messages. Generally, posts targeting individuals were rated as equally racist, but more honest, than posts targeting groups. Additionally, public anonymous posts were rated as less honest than other posts. These studies imply people may disregard anonymous expressions of prejudice, dismissing them as dishonest. These studies demonstrate that many people may not take anonymous online prejudiced rhetoric seriously, which could foster toxic online environments conducive to incitements of real-world violence against marginalized groups.
Keywords: Social Media; Prejudice; Anonymity